Implementasi Pembelajaran Sains Berbasis Alam Dalam Menstimulasi Berfikir Kritis Anak Usia 5-6 Tahun - Ulfatun Rohmah; Aprida, Siti Nurul; Adawiyah, Robiatul; Kurnia, Lita (LPPM STAI La Tansa Mashiro, 2025)
Many young children haven't had varied and meaningful experiences with nature-based science, even though nature provides numerous resources for early childhood learning. Nature is also a wonderful place for learning, allowing children to explore their surroundings. Many children also don't know that sprouts are made from mung beans, fermented using only the simple ingredient of mung beans.Therefore, this study aims to apply nature-based science learning to improve children's cognitive abilities through planting mung bean seeds in children aged 5-6 years at Buah Hati Ibu PAUD. The research method used was qualitative with descriptive methods. The subjects in this study were educators and children in group B. Data collection techniques were carried out through observation, interviews, and documentation.The results of the study show that the application of nature-based learning through the activity of planting mung bean seeds improves children's cognitive abilities. Children appear more enthusiastic and active, and are directly involved in every stage of the process, from planning to successful activities. This activity also builds self-confidence, independence, exploration, learning to plant mung bean seeds has been proven effective in developing critical thinking skills in children. In addition, children can also know the growth of sprouts/beans produced from mung beans.